2018
DOI: 10.1186/s13660-018-1937-y
|View full text |Cite
|
Sign up to set email alerts
|

Bohr-type inequalities of analytic functions

Abstract: In this paper, we investigate the Bohr-type radii for several different forms of Bohr-type inequalities of analytic functions in the unit disk, we also investigate the Bohr-type radius of the alternating series associated with the Taylor series of analytic functions. We will prove that most of the results are sharp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Furthermore, Kayumov and Ponnusamy [24] introduced and studied the Bohr-Rogosinski inequality and found the Bohr-Rogosinski radius. Based on the initiation of [23], several forms of Bohr-type inequalities for the family B were considered in [31] when the Taylor coefficients of classical Bohr inequality are partly or completely replaced by higher order derivatives of f . Let S r (f ) denote the area of the image of the subdisk |z| < r under the mapping f and when there is no confusion, we let for brevity S r for S r (f ).…”
Section: Theorem B ([37mentioning
confidence: 99%
“…Furthermore, Kayumov and Ponnusamy [24] introduced and studied the Bohr-Rogosinski inequality and found the Bohr-Rogosinski radius. Based on the initiation of [23], several forms of Bohr-type inequalities for the family B were considered in [31] when the Taylor coefficients of classical Bohr inequality are partly or completely replaced by higher order derivatives of f . Let S r (f ) denote the area of the image of the subdisk |z| < r under the mapping f and when there is no confusion, we let for brevity S r for S r (f ).…”
Section: Theorem B ([37mentioning
confidence: 99%
“…Therefore in Section 3, we mainly extend the Bohr radius for the family P. Moreover, the properties of M f (r) are extended to the alternating series A f (r), which was originally investigated in [4] by Ali et al In fact they have shown that if f ∈ B, then |A f (r)| < 1 holds for r ≤ 1/ √ 3. In addition, according to Liu et al in [26], the Bohr radius can be generalized by using the property of A f (r). Surprisingly, in recent papers, the authors in [17,24,33,34] refined the Bohr inequality in improved form by replacing…”
Section: Introductionmentioning
confidence: 99%
“…Known important theorems. Recently, Kayumov and Ponnusamy et al [21] (see also [32]) refined Theorem A in the following form whereas, Liu et al [26] proved the estimate of the alternating series.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the cases p = 1 and N = 2 were considered in [9]. Also, the situations m = 1 and p = 1 or 2 were investigated in [32]. For p = 1, 2 and N = 5, 10, 15, the values R m,N 8 (p) are computed in Table 8.…”
mentioning
confidence: 99%